A influência dos fatores estruturais na criação de valor público no governo digital brasileiro - Lopes, Karen Maria Gross (2021)
The world has gone digital. The phenomenon of digital transformation raises expectations and creates social pressure for more agile and simplified digital public services: there is an audience out there. The transformative effect of digital government is still contested. There is a paradox: there are many investments and little delivery of public value. The Covid-19 pandemic has accelerated and reinvigorated the role of digital government, as the use of digital services is spreading as social distance drives online interactions. Governments must serve the public interest, for the public, in the context of the public ethos. However, the public interest is diverse and controversial. Technologies are not free of value: digital government requires decisions and choices. Prioritizations are impacted by external and internal factors that influence public managers' decision making. As a result, leaders have a relevant role in the implementation of digital initiatives. When they adopt a position of public value, they are often based on values underlying the traditions of public administration. Within this context, this study deals with the application of public value as a driver of digital initiatives, and aims to analyze the factors that impact positions of public value in digital initiatives in Brazilian states. For this, a trajectory is adopted, through a logic explained in three articles, so that the results of the predecessor are inputs for the latter. The first is a theoretical essay that results in theoretical proposals to be adopted by the following. The second, a qualitative study to deliver a conceptual model, which is validated by the third article, with a quantitative approach. The findings show that the media is considered the only external agent that has relevant power in prioritizing digital initiatives. Among the internal structural factors, the fiscal crisis and budget restrictions combined with political factors also appear as relevant players in prioritizing, driving initiatives with a focus on efficiency and internal productivity. The rivalry between the positions is confirmed, demonstrating that competition exists and that the solution given, by public managers, remains with the imperative of administrative efficiency. The investigation also points out that governments do not prioritize listening to citizens and do not create spaces for citizen participation and collaboration. However, improving services for the citizen has had a positive impact on internal simplification. The counterintuitive finding, verified in the quantitative research, unlike the qualitative research, is that the political factors and the personnel factors have not had an effect on the prioritization for improvement in digital public services. The study, as a whole, connects the theoretical basis of the study of public value with the normative tendencies of research rhetoric and empirical validation over real practices in the context of digitalinitiatives in Brazilian states. The great contribution of this study is for the development of a scale for measuring public value based on the theory of public value and the framework of positions of public value. In addition, it adds new constructs and variables that explain how structuring factors 10 influence positions of public value in prioritizing digital government projects in Brazilian states. The main limitation of the study is that it only listened to public managers, thus, a new survey may include the collection of data on the perceptions of political agents, public servants, State suppliers and, especially, the arbitrator for the creation of public value, which is the citizen Brazilian.